Effectiveness of Ultrasound-guided Percutaneous Catheter Drainage for Pancreatic Fluid Collections: An Interventional Study - Hussain, Ameer; Faizal, Afwaan; Raj, Vishnu (Journal of clinical and diagnostic research, 2024)
Introduction: Pancreatic Fluid Collections (PFCs) are accumulations of pancreatic fluid or debris contained within a granulation tissue wall. Unlike true cysts, they arise as complications of various conditions like acute pancreatitis, abdominal trauma, pancreatic surgery, or chronic pancreatic duct obstruction. While smaller PFCs (under 4 cm) often resolve on their own without intervention, larger collections exceeding 6 cm or those causing symptoms like infection or bile duct obstruction have significantly lower rates of spontaneous resolution. In such cases, drainage intervention is typically recommended. Aim: To assess the treatment effectiveness of Percutaneous Catheter Drainage (PCD) for PFCs using ultrasound guidance. Materials and Methods: A prospective interventional study was conducted in the Department of Radiodiagnosis, Government Stanley Medical College and Hospital, Chennai, Tamil Nadu, India, from September 2021 to August 2022. The study focused on patients (N=73) with PFC as a complication of acute pancreatitis necessitating ultrasound-guided PCD. The study outcomes were clinical effectiveness, reinterventions, and mortality rates. Additionally, authors investigated the impact of various drainage factors, such as indication, PFC type, location relative to the pancreas, PFC size, Modified Computed Tomography (CT) Severity Index (CTSI), duration between symptom onset and PCD initiation, total catheter dwell time, and duration between symptom onset and reintervention. Statistical analyses employed International Business Machine (IBM) Statistical Packages for Social Sciences (SPSS) Statistics. Descriptive statistics and independent samples t-test for continuous variables; Chi-square test for categorical data (p<0.05). Results: In present study, the mean age of the subjects was 47 years. PCD in terms of clinical success was 63% (n=46) and clinical failure was 37% (n=27). Open necrosectomy was performed on 15 patients (20.5%) and open cystogastrostomy was performed on 11 patients (15.1%). Conclusion: The utilisation of ultrasound-guided PCD for PFCs represents a technique associated with relatively low morbidity and mortality rates. This approach can serve as either definitive treatment or a transitional measure before resorting to open surgery.